(untitled) (Actualizaciones en Sida e Infectología, 2024)
Introduction: Tocilizumab (TCZ) is an interleukin-6 receptor blocker proposed to treat severe or critical COVID-19 patients. This study aims to evaluate the clinical effects of TCZ administration in hospitalized patients with severe COVID-19. Additionally, the study investigates the most common adverse and infectious events associated with the use of TCZ. Materials and methods: Analytical, observational case-control study matched by age, sex, and comorbidities of adult patients with severe COVID-19, hospitalized between December 2020 and March 2021. Inclusion criteria: requirement for oxygen provision greater than or equal to 5 l/min to achieve saturation >93% and one of the following: stroke, myocardial infarction, BMI >30, chronic kidney disease, age >60 years, D-dimer >1000 ng/ml, or quantitative C-reactive protein >75 mg/l. Outcomes evaluated: all-cause mortality, transfer to critical care unit (CCU), and mechanical ventilatory assistance (MVA) requirement. Results The study included 320 patients, out of which 110 patients received TCZ in addition to corticosteroids (cases), while 210 patients were only exposed to corticosteroids (controls). The mortality rate was 29% in the cases group, compared to 44% in the control group (p=0.0081). Similarly, 48% of the cases were transferred to CCU, while 81% of the control group were transferred (p=0.0081). The requirement for mechanical ventilation (MVA) was 24% in the cases group and 56% in the control group (p=0.0001). Conclusion Patients treated with TCZ had a lower proportion of CCU use, MVA, and mortality compared to similar patients who did not receive it. These results are consistent with the current evidence.